Draft genome sequence of Burkholderia gladioli Coa14, a bacterium with petroleum bioremediation potential isolated from Coari Lake, Amazonas, Brazil - Lopes, Eraldo Ferreira; Da Costa, Josemar Gurgel; Wolf, Ivan Rodrigo [UNESP]; Lima, José Paulo de Araújo; Astolfi-Filho, Spartaco (American Society for Microbiology, 2018)
Burkholderia gladioli Coa14 is a bacterium isolated from water collected from Coari Lake (Amazonas, Brazil) that shows a capacity for survival in a medium containing only oil as a carbon source. Here, we report its draft genome sequence, highlighting some genes involved with petroleum derivative degradation.